2019
DOI: 10.3390/agronomy9100573
|View full text |Cite
|
Sign up to set email alerts
|

Closing Yield Gaps through Soil Improvement for Maize Production in Coastal Saline Soil

Abstract: As efforts to close crop production yield gaps increase, the need has emerged to identify cost-effective strategies to reduce yield losses through soil improvement. Maize (Zea mays L.) production in coastal saline soil is limited by high salinity and high pH, and a limited number of soil amendment options are available. We performed a field experiment in 2015 and 2016 to evaluate the ability of combined flue gas desulfurization gypsum and furfural residue application (CA) to reduce the maize yield gap and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…These effects can be explained by the reduction of soil salinity, which led to greater salt drainage from the root zone (Haque et al., 2018; X. Wang et al., 2018), followed by enhanced maize growth and yield formation (Dong, Yang, Zhang, et al., 2018; Farooq et al., 2015; J. Zhang et al., 2020). Previous studies have indicated that high ear density is a key parameter for high grain yield (Huang et al., 2019), and biomass accumulation from silking to maturity determines grain weight and grain yield (Srivastava et al., 2018; J. Zhang, Jiang, Xue, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects can be explained by the reduction of soil salinity, which led to greater salt drainage from the root zone (Haque et al., 2018; X. Wang et al., 2018), followed by enhanced maize growth and yield formation (Dong, Yang, Zhang, et al., 2018; Farooq et al., 2015; J. Zhang et al., 2020). Previous studies have indicated that high ear density is a key parameter for high grain yield (Huang et al., 2019), and biomass accumulation from silking to maturity determines grain weight and grain yield (Srivastava et al., 2018; J. Zhang, Jiang, Xue, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Total rainfall values in 2017, 2018, and 2019 during the experimental maize growing seasons (May–September) were 417, 809, and 461 mm; the total evaporation values were 485, 830, and 574 mm (Supplemental Figure S1; data provided by the China Meteorological Data Network). The soil texture was silt loam (J. Zhang, Jiang, Xue, et al., 2019) and the soil was slightly saline, with electrical conductivity (EC) values (a 1:5 ratio of soil/water) of 0.45–0.58 dS m −1 (Table 1) (J. Zhang, Jiang, Miao, et al., 2019). The chemical properties during 2017 in the 0‐to‐60‐cm soil depth at 20‐cm intervals are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the post-harvest CA treatment exhibited remarkable outcomes, with notable increases observed in calcium (Ca2+) and soil organic carbon (SOC) contents, while simultaneously reducing sodium (Na+) content and pH levels in the upper soil layer. Consequently, maize crops experienced significant enhancements in nitrogen, phosphorus, potassium, calcium, and magnesium accumulations, alongside a decrease in Na accumulation when compared to the control group [22]. Another noteworthy study delved into the dynamics of global maize production, consumption, and trade, aiming to decipher evolving trends over the past 25 years and their consequential impact on research and development (R&D), with a particular focus on the Global South.…”
Section: Soil Testing For Maize Productionmentioning
confidence: 99%
“…Several approaches to narrowing the yield gap have been studied. Zhang J. et al (2019) reported that improving soil properties could reduce the maize yield gap. Cui et al (2013) reported that effective N management could narrow the maize yield gap while reducing greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%